Maternity Room Action Innovation with “Sayyidah Maryam” - Durrotun Munafiah; Anita Indra Afriani; Fauziah Winda Gurnita (Health Notions, 2020)
Background: Childbirth is an unforgettable experience for women. Every woman wants a happy, healthy, comfortable pregnancy and childbirth experience. From the research, it was found that the environment is the biggest factor in the healing process in medical facilities, namely 40%. But unfortunately the environment that is formed by the existing maternity homes actually gives pregnant women fear, anxiety, boredom, and stress. Midwives as caregivers during childbirth should understand not only to pay attention to the medical needs of women giving birth but also to the psychological and emotional needs during the labor phase. Therefore, innovations regarding the development of delivery rooms and how to design delivery rooms that pay attention to the well-being of mothers and fetuses need to be developed. The delivery room design innovation was developed using the Sayyidah Maryam concept. The concept is the main formulation in the formation of scientific ideas inspired by Sayyidah Maryam binti Imron, a holy woman, the mother of the Prophet Isa Alaihi Salam, one of the role models for Muslim women. Purpose: to develop innovative delivery room designs that pay attention to the welfare of mothers and fetuses with the concept of Sayyidah Maryam. Methods: Innovation development research was carried out by means of research development. Results: The 3D image design and animation video embodiment of the innovative concept of the delivery room action room, the Sayyidah Maryam method based on literature and experimental tests, can increase the comfort of mothers spiritually and psychologically in the delivery process. Keywords: delivery room; action room; Sayyidah Maryam